TRANSFORMASI KEBIJAKAN PENDIDIKAN MELALUI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Olan Sulistia Rambung; Sion Sion; Bungamawelona Bungamawelona; Yosinta Banne Puang; Silva Salenda (JIP: Jurnal Ilmu Pendidikan, 2023)
Educational transformation is a fundamental change in the approach, methods, and goals of education to address the demands of the modern era. The concept of a "kurikulum merdeka" (free curriculum) becomes a central pillar in this endeavor. A free curriculum emphasizes active student engagement, granting them autonomy in planning, directing, and evaluating their learning. The interdisciplinary approach in educational transformation necessitates the integration of elements from various disciplines to provide a holistic and contextual understanding. This prepares students to confront real-world issues with diverse perspectives and innovative solutions. The significance of 21st-century skills in a free curriculum and educational transformation assists students in developing competencies relevant to the evolving demands of the workforce. Creativity, critical thinking, collaboration, digital literacy, and self-directed learning take precedence. Through educational transformation and a free curriculum, students become active participants in the learning process. They play a role in determining interests, planning learning activities, and assessing progress. Teachers assume roles as guides and facilitators, assisting students in developing independent and critical skills. This approach not only readies students to face the complexities of the job market but also teaches them to think across disciplines, innovate, collaborate, and address real-world challenges. Educational transformation and a free curriculum play a role in creating an inclusive, relevant, and responsive learning environment for the needs of future generations.